Factors affecting biochemical recurrence of prostate cancer after radical prostatectomy in patients with positive and negative surgical margin - Celik, Serdar (Prostate Int, 2020)
PURPOSE: To investigate the clinical and pathological predictive factors affecting biochemical recurrence (BCR) after radical prostatectomy (RP) in patients with positive and negative surgical margin (SM). METHODS: Patients who underwent RP were retrospectively reviewed for the study. Demographic, clinical, pathological and oncological data were evaluated. All data were compared between patients with positive SM and negative SM to detect factors associated with SM status. Later, patients were divided into two groups as BCR-negative and BCR-positive groups. Data were separately compared between BCR groups for all patients, SM-negative and SM-positive patients, respectively. RESULTS: A total of 254 patients with a mean age of 63.5 years and the mean prostate-specific antigen of 10.9 ng/ml were evaluated in the study. SM positivity was found to be an independent prognostic factor for BCR (p = 0.013, Odds Ratio (OR): 0.267, 95% Confidence Interval (CI): 0.094-0.755). In SM-positive patients, biopsy Gleason Score and International Society of Urological Pathology grade were found to be independent predictive factors for BCR (p < 0.05). However, only tumor to SM distance (TSMD) was found to be an independent risk factor for BCR (p = 0.024) in SM-negative patients. The predictive cutoff value of the TSMD was found to be 75 μm for BCR (100% sensitivity and 63.9% specificity) (AUC = 0.803, p = 0.024). Although all of 46 patients with >75 μm TSMD were recurrence free, 5 of 31 patients with <75 μm TSMD had BCR (p = 0.009; OR: 0.839 CI: 0.719–0.979). CONCLUSION: High Gleason Score and International Society of Urological Pathology grade of biopsy were found to be associated with BCR in SM-positive patients. For SM-negative patients, only TSMD was found to be associated with BCR after RP.